Financial and Non-Financial Incentive Mechanisms in ISPO Certification: A Management Control Systems Perspective - Antonius Grivaldi Sondakh; Lili Safrida; Diah Fitriaty; Muhammad Yasin (Invoice : Jurnal Ilmu Akuntansi, 2026)
Sustainability certification has become a key governance instrument for aligning dispersed actors with environmental and regulatory objectives, particularly in agricultural value chains. However, the effectiveness of incentive mechanisms designed to support certification adoption remains insufficiently understood, especially when different types of incentives are evaluated within an integrated framework. Drawing on a management control systems (MCS) perspective, this study examines the comparative effects of financial, non-financial, and combination incentives on independent smallholders’ perceived effectiveness of support for Indonesian Sustainable Palm Oil (ISPO) certification. This study adopts a quantitative explanatory approach using survey data collected from 143 oil palm smallholders in South Kalimantan, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the relationships between incentive mechanisms and perceived effectiveness. The findings reveal that all three types of incentives have a positive and statistically significant influence. However, non-financial incentives demonstrate the strongest effect (β = 0.352, p < 0.001), followed by financial incentives (β = 0.261, p < 0.001), while combination incentives show a weaker effect (β = 0.165, p < 0.05). These results suggest that enabling controls, such as training, market access facilitation, and institutional recognition, play a more critical role than outcome-based financial incentives in shaping perceived effectiveness. Furthermore, the findings challenge the assumption of automatic complementarity in combined incentive designs, indicating that integration does not necessarily enhance effectiveness in fragmented institutional contexts. This study contributes to management accounting literature by extending the concept of control packages to extra-organizational sustainability governance and highlights the conditional nature of incentive complementarity. The findings offer important implications for designing more coherent and effective sustainability-oriented policy interventions in developing economies.